The impact of news and the SMP on realized (co)variances in the eurozone sovereign debt market - Roel Beetsma; Frank de Jong; Massimo Giuliodori; Daniel Widijanto (European Central Bank (ECB), 2014)
We use realised variances and co-variances based on intraday data from Eurozone sovereign bond market to measure the dependence structure of eurozone sovereign yields. Our analysis focuses on the impact of news, obtained from the Eurointelligence newsflash, on the dependence structure. More news raises the volatility of interest rates of financially distressed countries and decreases the covariance of distressed countries' yields with German bond yields, suggesting a flight-to-quality effect. Common news about the euro crisis and news about specific countries itself tend to raise the covariance of yields between distressed countries, indicating potential crisis spillover effects. However, we do not detect spillover effects from news about third countries to the covariance between other country pairs. Bond purchases by the ECB under its Securities Markets Programme (SMP) mitigate the negative crisis spillovers among the distressed countries and reduce the flight-to-safety from the distressed countries to Germany.
Keywords: E62; G01; G12; G15; H63; 330; crisis; eurozone; realized covariances; SMP; sovereign debt; Spillovers; Rendite; Öffentliche Anleihe; Varianzanalyse; Wirtschaftsinformation; Schuldenkrise; Offenmarktpolitik; Eurozone; EU-Staaten